Proceedings of the 2019 ACM Symposium on Principles of Distributed Computing 2019
DOI: 10.1145/3293611.3331569
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity Lower Bounds in Broadcast Congested Clique

Abstract: We prove three new lower bounds for graph connectivity in the 1-bit broadcast congested clique model, BCC(1). First, in the KT-0 version of BCC(1), in which nodes are aware of neighbors only through port numbers, we show an Ω(log n) round lower bound for Connectivity even for constant-error randomized Monte Carlo algorithms. The deterministic version of this result can be obtained via the well-known "edge-crossing" argument, but, the randomized version of this result requires establishing new combinatorial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…At the core of their approach is an indistinguishability argument that uses edge crossings. Edge crossings have been used numerous times to prove a variety of distributed computing lower bounds (see [19,20,28,30,32] for some examples). However, in the KT-1 Congest model, indistinguishability arguments via edge crossing are more challenging because when an edge incident on a node is crossed, the node is exposed to a new ID due to KT-1.…”
Section: Technical Contributionsmentioning
confidence: 99%
“…At the core of their approach is an indistinguishability argument that uses edge crossings. Edge crossings have been used numerous times to prove a variety of distributed computing lower bounds (see [19,20,28,30,32] for some examples). However, in the KT-1 Congest model, indistinguishability arguments via edge crossing are more challenging because when an edge incident on a node is crossed, the node is exposed to a new ID due to KT-1.…”
Section: Technical Contributionsmentioning
confidence: 99%
“…For randomized algorithms, the AGM sketch [AGM12] solves the problem with only one round in BCAST(log 3 n). Pai and Pemmaraju [PP19] proved an Ω( 1 b log n) round lower bound in BCAST(b) for deterministic connectivity algorithms. They also showed the same lower bound for random algorithms that compute the connected components of G. To the best of our knowledge, Theorem 1 is the first nontrivial lower bound for connectivity in BCAST(b) for b = ω(log n), even for deterministic algorithms (it implies that if b = o(log 3 n), then we need at least two rounds).…”
Section: Related Workmentioning
confidence: 99%
“…There has been a lot of progress in solving various problems in the CCM including minimum spanning tree (MST) [1,8,9,10], facility location [11,12], shortest paths and distances [13,14,15], subgraph detection [16], triangle finding [16,17], sorting [18,19], routing [19], and ruling sets [8,11]. Recently Pai and Pemmaraju [20] studied the graph connectivity lower bounds in the CCM. Specifically they showed that the lower bound round complexity for graph connectivity problem in the BCCM(1) 2 , which is Ω(log n), holds for both deterministic as well as constant-error randomized Monte Carlo algorithms [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently Pai and Pemmaraju [20] studied the graph connectivity lower bounds in the CCM. Specifically they showed that the lower bound round complexity for graph connectivity problem in the BCCM(1) 2 , which is Ω(log n), holds for both deterministic as well as constant-error randomized Monte Carlo algorithms [20]. Despite the fact that the ST problem has been extensively studied in the CONGEST model of distributed computing [22,23,24,25,26], to the best of our knowledge, such a study has not been carried out in the CCM.…”
Section: Introductionmentioning
confidence: 99%